2007
DOI: 10.1247/csf.07015
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Constituting Blood-nerve Barrier Have Highly Specialized Characteristics as Barrier-forming Cells

Abstract: ABSTRACT. In autoimmune disorders of the peripheral nervous system (PNS) such as Guillain-Barré syndrome and chronic inflammatory demyelinating polyradiculoneuropathy, breakdown of the blood-nerve barrier (BNB) has been considered as a key step in the disease process. Hence, it is important to know the cellular property of peripheral nerve microvascular endothelial cells (PnMECs) constituting the bulk of BNB. Although many in vitro models of the blood-brain barrier (BBB) have been established, very few in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 44 publications
4
43
0
Order By: Relevance
“…We previously described that the same transporters were expressed in rat PnMECs (Sano et al, 2007). GLUT-1 and p-gp have been demonstrated to present on microvessels in the endoneurium of rat sciatic nerves by an immunohistochemical analysis (Sano et al, 2007). The FH-BNBs in the present study also expressed MDR-1, MRP-1 and GLUT-1.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…We previously described that the same transporters were expressed in rat PnMECs (Sano et al, 2007). GLUT-1 and p-gp have been demonstrated to present on microvessels in the endoneurium of rat sciatic nerves by an immunohistochemical analysis (Sano et al, 2007). The FH-BNBs in the present study also expressed MDR-1, MRP-1 and GLUT-1.…”
Section: Discussionsupporting
confidence: 75%
“…Previous reports have indicated that PnMECs in human sural nerves express occludin, claudin-5 and ZO-1 (Kanda et al, 2004), and claudin-1 was detected in perineurium (Hirakawa et al, 2003), primary human PnMECs (Yosef et al, 2010) and human Schwann cells (Alanne et al, 2009). We also reported that rat PnMECs expressed many molecules forming tight junctions (Sano et al, 2007). FH-BNBs expressed all of the important molecules for maintaining tight junctions at the mRNA level, and contained occludin, claudin-5, ZO-1 and ZO-2 at the cell-cell boundaries at the protein level.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Microangiopathy of the endoneurium is a common finding in the nerves of diabetic patients, and is thought to be a contributing factor to the development of diabetic neuropathy. The blood-nerve barrier (BNB) is localised in the microvessels of the endoneurium or perineurium, and consists of peripheral nerve microvascular endothelial cells (PnMECs), pericytes of endoneurial microvascular origin, and the basement membrane [1][2][3]. The basement membrane of the BNB plays important roles in maintaining the structure and function of capillary vessels [4].…”
Section: Introductionmentioning
confidence: 99%